Pengembangan Media Pembelajaran Pencak Silat Berbasis Aplikasi Teknologi Digital Virtual Reality - nelson, sonya; Septri, Septri; Sari, Dessi Novita (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
Virtual reality is a technology that allows users to enter and interact in a virtual world, because virtual reality is a computer technology that combines special input and output devices so that users can interact deeply with virtual environments as if they were in the real world. This virtual reality-based pencak silat basic technique learning media can be used by students anytime and anywhere so that students can learn without being limited by space and time. The purpose of this research is to develop pencak silat learning materials in terms of practicality, attractiveness and use value. The research development model uses Borg and Gall, with stages, namely: (1) Data collection; (2) Planning (3) Development; (4) Design validation (5) Design review (6) Product testing (7) Product evaluation (8) Usage testing (9) Product evaluation (10) Mass production. The results of the study according to the results of expert confirmation of the development of virtual reality-based pencak silat learning materials show very good results and can be used as learning materials. The average assessment results obtained by experts amounted to 86.3%. Student response to the use of this media in learning pencak silat is very good with the acquisition of scores in the small group test of 88.4% in the large group test of 89.1%